Abrodictyum polynesicum (Hymenophyllaceae, Polypodiidae), a new fern species for the French Polynesia - Dubuisson, Jean-Yves; Zhao, Ya-Nan; Boucheron-Dubuisson, Elodie; Ebihara, Atsushi (Phytotaxa, 2026)
The filmy fern Abrodictyum asae-grayi (Hymenophyllaceae) is thought to be distributed from New Guinea to French Polynesia. However, specimens from the Marquesas Islands and some populations from the Society Islands show clearly erect rhizomes, while the species A. asae-grayi is described as having creeping rhizomes. In-depth examination of the herbarium specimens and phylogenetic analysis demonstrate that the specimens with creeping rhizomes and those with erect rhizomes define two distinct species. The new species, A. polynesicum, endemic to French Polynesia, is discussed and described here.